Integration of pharmacodynamics, metabolomics and network pharmacology to elucidate the effect of Prunella vulgaris seed oil in the treatment of hyperlipidemia - Min Zeng; Xinyi Qin; Tao Yi; Zixuan Liu; Chengfeng Li; Shuna Tan; Shuai Zhang; Tongxin Xie; Jingchen Xie; Ping Wu; Zhimin Zhang (Arabian Journal of Chemistry, 2024)
To investigate the lipid-lowering activity of PVSO (a natural oil derived from the mature seeds of Prunella vulgaris L.), supercritical CO2 extraction technology was used to extract, and the components were characterized using GC–MS/MS and LC-MS/MS techniques. The lipid-lowering activity of PVSO was evaluated in vitro and in vivo. The results indicated that the supercritical CO2 extraction rate of PVSO was 16.63 %, and the ratio of linolenic acid to linoleic acid was 3:1. In addition, PVSO also contains bioactive components such as phenols, terpenes, flavonoids, and squalene. In vitro experiments showed that PVSO has a strong inhibitory effect on porcine pancreatic lipase, cholesterol esterase, and cholesterol micellization in a significant dose-dependent manner. In vivo experiments showed that PVSO (500 and 800 mg/kg) intervention markedly attenuated body-weight gain, liver weights, hepatic steatosis, oxidative stress biomarkers, and dyslipidemia induced by HFD (p < 0.05). Serum metabolomics studies revealed that 29 endogenous metabolites were significantly altered by HFD and recovered following intervention with PVSO (p < 0.05). PVSO suppressed hyperlipidemia mainly by regulating oxidative stress, choline metabolism, glycine, serine and threonine metabolism, and cholesterol metabolism. Combining metabolomics and network pharmacology analysis, 17 intersection targets, 21 GO and 6 KEGG pathways were obtained. Molecular docking showed that ACHE, CPT1A, HMGCR, LYPLA1, and PLD2 were the key targets of PVSO against hyperlipidemia. In summary, PVSO might be a potential active resource to prevent oxidative stress and lipid metabolism disorders in HFD-induced hyperlipidemia.